2003
DOI: 10.1073/pnas.0937302100
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic and lusitropic effects of HNO/NO in failing hearts: Independence from β-adrenergic signaling

Abstract: Nitroxyl anion (HNO͞NO ؊ ), the one-electron reduced form of nitric oxide (NO), induces positive cardiac inotropy and selective venodilation in the normal in vivo circulation. Here we tested whether HNO͞NO ؊ augments systolic and diastolic function of failing hearts, and whether contrary to NO͞nitrates such modulation enhances rather than blunts ␤-adrenergic stimulation and is accompanied by increased plasma calcitonin gene-related peptide (CGRP). HNO͞NO ؊ generated by Angelis' salt (AS) was infused (10 g͞kg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
292
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(310 citation statements)
references
References 47 publications
17
292
0
1
Order By: Relevance
“…Similar to NO ⅐ and NO ϩ , HNO is a potent inducer of the antioxidant protein heme oxygenase 1 (8), exhibits vasorelaxant properties (9), and modulates the activity of thiol-containing proteins, such as aldehyde dehydrogenase (10,11) and the N-methyl-D-aspartate receptor (12,13). In in vivo experiments, Paolocci et al (14) observed that HNO exerts positive inotropic and lusitropic action, which unlike NO ⅐ and nitrates is independent and additive to ␤-adrenergic stimulation and increases the release of plasma calcitonin gene-related peptide; these results suggest that donors of HNO are potential prodrugs for the treatment of heart failure (14). At high doses, HNO has been shown to induce DNA singlestrand breakage (15,16) and a concentration-dependent cytotoxicity in murine thymocytes (16).…”
mentioning
confidence: 99%
“…Similar to NO ⅐ and NO ϩ , HNO is a potent inducer of the antioxidant protein heme oxygenase 1 (8), exhibits vasorelaxant properties (9), and modulates the activity of thiol-containing proteins, such as aldehyde dehydrogenase (10,11) and the N-methyl-D-aspartate receptor (12,13). In in vivo experiments, Paolocci et al (14) observed that HNO exerts positive inotropic and lusitropic action, which unlike NO ⅐ and nitrates is independent and additive to ␤-adrenergic stimulation and increases the release of plasma calcitonin gene-related peptide; these results suggest that donors of HNO are potential prodrugs for the treatment of heart failure (14). At high doses, HNO has been shown to induce DNA singlestrand breakage (15,16) and a concentration-dependent cytotoxicity in murine thymocytes (16).…”
mentioning
confidence: 99%
“…4 More importantly, HNO can increase systolic force and decrease diastolic pressure in both normal and failing canine hearts through upregulating calcitonin gene-related peptide. 5 Thus, more and more examinations suggest that HNO may provide a powerful therapeutic agent for heart failure cure. Despite biochemical studies have proposed some biosynthetic pathways, for instance, HNO can be formed directly from NO and H2S via a redox reaction.…”
mentioning
confidence: 99%
“…Increased vascular tone, a typical feature of most forms of hypertension, has been associated with impaired NO signaling. Although the main mechanism of vasodilatation induced by the ruthenium-derived NO donors is due to K + channel activation and membrane hyperpolarization in normotensive rat aorta, we have reported that none of the K + channel subtypes are activated by the NO donor trans-[RuCl( [15] aneN 4 )NO] 2+ in the aorta from renal hypertensive rats (35). These results demonstrate that in this model of hypertension, impaired K + channels can contribute to decreased vasodilatation in response to NO.…”
Section: Potassium Channelmentioning
confidence: 99%
“…Lunardi et al www.bjournal.com.br nitrovasodilators, which are clinically used to control hypertensive crisis, protect patients from attacks of angina pectoris, and unload the heart during acute heart failure. Numerous other compounds, including NONOates, are available for the experimental generation of NO (3,4). Several NO donors have been used in clinical settings for decades (e.g., nitroglycerin and sodium nitroprusside).…”
Section: Introductionmentioning
confidence: 99%